Perancangan User Experience Website Marketplace dan Pemetaan Hasil Pertanian menggunakan Metode Five Planes - Mahatva Zenggi Maggenta; Riswan Septriayadi Sianturi; Agi Putra Kharisma (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Farmers often have difficulty in marketing their agricultural products. Besides the small market, the game of middlemen is the biggest enemy for the farmers. So that in buying and selling activities, farmers receive sales results far from the actual profit. The solution to these problems, researchers provide a solution that is offered, namely a website platform Mepisar.id. Through the website, it will be able to contain information regarding education and price monitoring, mapping of commodity yields in an area. The five planes method is the approach method used in this study. The goal is to create application designs according to user needs. The evaluation carried out got a good usability value. The usability values ​​obtained include the effectiveness aspect from the user's side, getting a score of 88%, and from the seller's side it gets a value of 89%. Then the efficiency aspect from the user's side gets a value of 0.105 goals/sec, and from the seller's side it gets a value of 0.094 goals/sec. For the satisfaction aspect using the usability scale (SUS) system, the user gets a score of 91.5 and the seller gets a score of 85 with grade A, adjective excellent, acceptable, and promoter. The UEQ results on the attractiveness aspect got a score of 2.85. Perspicuity aspect got a score of 2.88. The efficiency aspect gets a value of 2.85. Dependability aspect got a value of 2.90. The stimulation aspect got a score of 2.83 and the novelty aspect got a score of 2.58 which was converted into a benchmark scale into the excellent category.